2020
DOI: 10.1002/jclp.22972
|View full text |Cite
|
Sign up to set email alerts
|

Examination of a novel measure of trauma‐related drinking to cope

Abstract: Objectives The present study sought to fill a gap in the current literature by developing a concise self‐report questionnaire assessing drinking motives specific to coping with symptoms of posttraumatic stress disorder (PTSD). This new four‐item questionnaire is called the Trauma Related Drinking questionnaire (TRD). Method Using structural equation modeling, the latent structure of the TRD items and how they relate to other variables of interest were explored among a sample of 1,896 college undergraduates fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…These results align with findings from a number of studies that have also found that coping-related drinking mediated the relation between PTSD and a variety of alcohol use outcomes (e.g., Aarstad-Martin & Boyraz, 2017; Hawn, Bountress, et al, 2020; McDevitt-Murphy et al, 2017). Consistent with the self-medication hypothesis, the findings from this study continue to underline the importance of coping motives as a significant and powerful influence in the PTSD and harmful alcohol use relationship.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These results align with findings from a number of studies that have also found that coping-related drinking mediated the relation between PTSD and a variety of alcohol use outcomes (e.g., Aarstad-Martin & Boyraz, 2017; Hawn, Bountress, et al, 2020; McDevitt-Murphy et al, 2017). Consistent with the self-medication hypothesis, the findings from this study continue to underline the importance of coping motives as a significant and powerful influence in the PTSD and harmful alcohol use relationship.…”
Section: Discussionsupporting
confidence: 89%
“…Among veterans, coping motives have been shown to mediate the relation between PTSD and alcohol consequences (Miller et al, 2017), hazardous drinking (McDevitt-Murphy et al, 2017), alcohol consumption, frequency of use, and heavy drinking (McCabe et al, 2019). In college student samples, coping motives also mediated the relation between PTSD and risky drinking (Aarstad-Martin & Boyraz, 2017) and between alcohol use and problems (Hawn, Bountress, et al, 2020). Additionally, Hawn, Bountress, et al (2020) found that a more specific measure of “trauma-related drinking to cope” partially mediated the relation between PTSD and alcohol use problems among college students.…”
Section: Self-medication Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Correlational analyses and descriptive statistics are provided in Table 1. Interpretation of sample means as well as differences in the distribution of TRD and other variables among individuals exceeding and not exceeding the PCL-5 and AUDIT cutoff scores are provided in the TRD psychometric article (Hawn et al, 2020). As hypothesized, all constructs included in the full model were significantly associated with one another.…”
Section: Resultsmentioning
confidence: 99%
“…Cronbach’s alpha calculated from the LEAU sample suggested that the TRD items demonstrated good internal consistency (.88). The psychometric properties of TRD, as well as detailed information about the wording of the four TRD items and the response scale used, have been reported on in detail elsewhere (Hawn, Aggen, Cusack, et al, 2020). Response items from the TRD measure were summed to create a continuous score.…”
Section: Methodsmentioning
confidence: 99%